2020
DOI: 10.18535/jmscr/v8i1.01
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and the Outcome of Twin Pregnancies in a South-South Nigerian Tertiary Hospital

Abstract: Twinning is the commonest form of multiple pregnancy, and it is associated with increased adverse perinatal and maternal outcomes. A 5-year retrospective observational study of all cases of twin gestations delivered at the University of Uyo Teaching Hospital was conducted to determine the prevalence as well as document the maternal and perinatal outcomes associated with it. There were 219 twin deliveries during the study period, accounting for 2.17% of all deliveries. Twinning accounted for 98.65% of all multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…10 According to their study the high twinning in the Igbo-Ora diet was due to ilasa (okra leaf) soup eaten with amala (yam or cassava flour) or the community's water which must be used for various purposes in addition to cooking to have the intended effect. 10, 17 Furthermore, this qualitative study, reported that the cause of dizygotic twinning may follow the eating of Amala & ilasa (okra leaves), influence by twin deity, physical residence in Igbo-Ora, eating of bananas, the care respect & the celebration of twins, eating of cassava flour, eating of fresh food, soil of Igbo Ora, use of Ilasa Water, eating of melon (egusi) leaves and eating of Yam. 10 Borokini et al in 2022 investigated the significance of the Okra plant leaf (Abelmoschus esculentus Moench L) in multiple births, and the Okra leaf included significant minerals and phytochemicals that perform biological protective effects against free radicals, thus alleviating oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…10 According to their study the high twinning in the Igbo-Ora diet was due to ilasa (okra leaf) soup eaten with amala (yam or cassava flour) or the community's water which must be used for various purposes in addition to cooking to have the intended effect. 10, 17 Furthermore, this qualitative study, reported that the cause of dizygotic twinning may follow the eating of Amala & ilasa (okra leaves), influence by twin deity, physical residence in Igbo-Ora, eating of bananas, the care respect & the celebration of twins, eating of cassava flour, eating of fresh food, soil of Igbo Ora, use of Ilasa Water, eating of melon (egusi) leaves and eating of Yam. 10 Borokini et al in 2022 investigated the significance of the Okra plant leaf (Abelmoschus esculentus Moench L) in multiple births, and the Okra leaf included significant minerals and phytochemicals that perform biological protective effects against free radicals, thus alleviating oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…was exactly the same rate in the recent past years of 2005 to 2011 in this study accounting for 21.7 per 1,000 of all deliveries. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation